The History of the Spread of Islam Through Wayang Art - Sumawinata, Shiska; Suryana, Toto; Subakti, Ganjar Eka (Universitas Islam Negeri Raden Intan Lampung, 2022)
This article contains a discussion of the history of the spread of Islam through wayang art that developed in Nusantara. The writing of this article aims to explain the early arrival of Islam to Nusantara, the origin of wayang as a medium for the spread of Islam, to the role of wayang in the spread of Islam. In the preparation of this article, the author uses the literature study method to find and collect various relevant sources. Regarding wayang art, there are various Islamic religious values that can be found from wayang. The use of wayang as a medium for spreading Islam is thought to be inseparable from the initial position of wayang as an artistic performance used to spread religious, philosophical, and ethical teachings to humans. In addition, at that time wayang were also very popular with the public. The role of wayang in the spread of Islam is so important and this cannot be separated from the role of Wali Songo. Among them there are Sunan Giri, Sunan Kalijaga, and Sunan Bonang who preach using modified wayang as their medium. Both in terms of form and wayang stories have been adapted to Islamic teachings. When wayang has been adapted to Islamic teachings, people continue to like the art of wayang performed and can accept Islamic teachings easily. Keywords: Spread of Islam, Wali Songo, Wayang.